Structural relaxation in chalcogenide glasses - Málek, Jiří (Wiley-Blackwell, 2023)
The structural relaxation of chalcogenide glasses is discussed within Tool-Narayanaswamy-Moynihan (TNM) formalism. The TNM parameters for more than 70 different glassy compositions are compared on the basis of the relaxation rate defined as R-f(Delta T) = -(dT(f)/dlogt)(i) at the inflection point of the isothermal relaxation curve plotted on a logarithmic timescale. The R-f(Delta T) depends on the TNM parameter ss and the parameter sigma, combining the nonlinearity parameter x, the effective activation energy h* or the fragility m. It is shown that R-f(10) estimated at 10 K below T-g is useful for the prediction of structural relaxation kinetics in different amorphous materials. The chalcogenide glasses are, for example, compared with oxide glasses and organic polymers. For all these materials, the R-f(10) versus sigma plot shows a well-defined pattern that is thoroughly discussed.
Strukturní relaxace v chalkogenidových sklech
Keywords: chalcogenides; glass transition; viscosity; chalkogenidy; skelný přechod; viskozita